Efektivitas Konsentrasi Media MS dan Pupuk Cipmape terhadap Pertumbuhan Buah Naga (Hylocereus polyrhizus) Secara In Vitro - Miratul Hikmah; Primadiyanti Arsela; Ardaniah Ardaniah (Fakultas Pertanian, Universitas Pattimura Ambon, Indonesia, 2025)
The demand for the dragon fruit market is increasing, and limited land is an obstacle to conventional dragon fruit propagation. Dragon fruit production also needs to be increased; the solution to get a sufficient supply of seedlings in a short time can be supported by tissue culture propagation. One of the determining factors for plant propagation with tissue culture is to find the proper propagation media. The purpose of this study was to determine the effect of the MS media and Cipmape fertilizer concentration and the interaction between the two on the growth of dragon fruit explants. This research was carried out from March through May 2025 at the tissue culture laboratory, Faculty of Agriculture and Digital Business, Universitas Muhammadiyah Kalimantan Timur. This study was conducted using the 2-factor complete random design (CRD). 16 combinations repeated 5 times in a total of 80 bottles as sampled. Each bottle contains 5 seeds. The results showed that MS 1/6 medium produced the fastest bud initiation at 8 days after culture (DAC) and the highest bud growth with average heights of 2.54 cm (3 weeks after culture, WAC), 3.48 cm (4 WAC), and 4.18 cm (5 WAC). MS 1/4 medium also supported early growth with a bud height of 1.52 cm at 2 WAC. The application of Cipmape fertilizer at 1 g·L⁻¹ resulted in the best growth, with bud height reaching 3.48 cm at 4 WAC and an average root number of 1.40 at 3 WAC. The survival rate of explants reached 97.5% with only 2.5% contamination. Meanwhile, the interaction factor showed a significant effect at 2 WAC on bud height parameters.